Inflammatory Bowel Disease in the Obese Patient - Boutros, Marylise (Thieme Medical Publishers, 2011)
Obesity is becoming increasingly more common among patients with inflammatory bowel disease. In this review, we will explore the epidemiological trends of inflammatory bowel disease, the complex interplay between the proinflammatory state of obesity and inflammatory bowel disease, outcomes of surgery for inflammatory bowel disease in obese as compared with non-obese patients, and technical concerns pertaining to restorative proctocolectomy and ileoanal pouch reservoir, stoma creation and laparoscopic surgery for inflammatory bowel disease in obese patients.